2007
DOI: 10.1016/j.brainres.2007.02.076
|View full text |Cite
|
Sign up to set email alerts
|

Lexical ambiguity in sentence comprehension

Abstract: An event-related fMRI paradigm was used to investigate brain activity during the reading of sentences containing either a lexically ambiguous word or an unambiguous control word.Higher levels of activation occurred during the reading of sentences containing a lexical ambiguity. Furthermore, the activated cortical network differed, depending on: (1) whether the sentence contained a balanced (i.e., both meanings equally likely) or a biased (i.e., one meaning more likely than other meanings) ambiguous word; and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
119
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 63 publications
16
119
0
4
Order By: Relevance
“…More recently, Bilenko et al (2008), showed that increased processing resources recruit areas in the inferior frontal gyrus bilaterally under conditions of competition, even when the experimental task does not impose overt selection (see also Mason andJust, 2007 andRodd et al, 2005). The present study not only provides further support to these findings, but succeeds in further delineating the specific area within the IFG that is involved in such processing.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…More recently, Bilenko et al (2008), showed that increased processing resources recruit areas in the inferior frontal gyrus bilaterally under conditions of competition, even when the experimental task does not impose overt selection (see also Mason andJust, 2007 andRodd et al, 2005). The present study not only provides further support to these findings, but succeeds in further delineating the specific area within the IFG that is involved in such processing.…”
Section: Discussionsupporting
confidence: 80%
“…Several neuroimaging studies (Kan & Thompson-Schill, 2004;Petrides et al, 1995;Thompson-Schill et al, 2002;Thompson-Schill, D'Esposito, & Kan, 1999 Mason andJust, 2007 andRodd et al, 2005 for similar findings in the presence of sentential context).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Neuroimaging studies have examined the relation between cognitive abilities (e.g., Just, Carpenter, & Miyake, 2003), speech perception and brain activity (e.g., Mason & Just, 2007;Osaka et al, 2003). These studies indicate that RSpan can explain individual differences in the efficiency of processes (attentional or lexical) relevant for understanding degraded speech.…”
Section: Introductionmentioning
confidence: 99%
“…In the violation detection task (Ni et al, 2000), semantic processing may terminate earlier in the incongruent condition than in the congruent condition due to a specific reading strategy (Huang et al, 2012;Zhu et al, 2009). Although activation in the LIFG has been reported in a wide range of tasks, including semantic congruency judgment (Constable et al, 2004;Rueschemeyer et al, 2006;Zhu et al, 2009), meaningfulness rating (Humphries et al, 2007), reading for comprehension (Hagoort et al, 2004;Tesink et al, 2009), comprehension probe test (Just et al, 1996;Mason and Just, 2007;Newman et al, 2009;Ye and Zhou, 2009), priming (Devauchelle et al, 2009), and violation detection (Ni et al, 2000), it has been suggested that these tasks all involve explicit attentional control (Crinion et al, 2003;Van Petten and Luka, 2006). It is possible that such control processes may interact with semantic unification and constitute an alternative explanation for the LIFG activations observed in these studies.…”
Section: Introductionmentioning
confidence: 99%